INCREASING STUDENTS’ LEARNING OUTCOMES ON THE VOLUME OF CUBES AND BEAMS LEARNING MATERIAL USING PROBLEM-BASED LEARNING MODEL - Anik Sundari; Vinencia Ika Indralin; Siti Dewi Maharani (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This paper discusses a type of Classroom Action Research (CAR), which is based on the low students’ Mathematics learning outcomes of students in class V.B at SD Negeri 112 Palembang. The purpose of this research is to improve students’ learning outcomes through the implementation of the Problem-Based Learning (PBL) model. The research was conducted in two cycles, with each cycle consisting of four stages: planning, action, observation, and reflection. The techniques used to collect data were observation, tests, and documentation. The initial condition of the research showed that the percentage of students’ learning completeness was only 10.34% (Very Less), which subsequently increased in the first cycle to 55.17% (Sufficient). Students’ learning outcomes further improved in the second cycle, with the percentage of learning completeness reaching 89.66% (Very Good). The results indicate that the application of the PBL model in learning has a significant effect on improving students’ learning outcomes in class V.B, particularly on the topic of the volume of cubes and beams. Thus, the PBL model can be considered one of the effective learning models for improving students’ learning outcomes, especially when it continues to be examined and adapted in line with educational developments.